MISKIN TETAPI EFISIEN ? SUATU TELAAH TERHADAP FUNGSI PRODUKSI PADI - Harianto Harianto; Dwi Astuti Bertha Susila (Departemen Agribisnis, FEM-IPB, 2008)
The objective of this study is to evaluate whether rice farming in Indonesia has been efficient in utilizing production inputs. This study also analyzes whether the farmers are responsive to the changing on output and inputs prices. The rice farming is taken as a case study because up to present rice is still an important and strategic commodity in Indonesia. Rice is also a commodity that poses lots of government intervention.Data used in this study were data at household level that have been collected through Patanas (National Farmers Panel) project. Based on data analysis, it showed that efficiency of rice farming in Indonesia needs to be improved more. Farmers applied too much labor for their rice farming, especially women labor. Farmers showed a significant responsiveness to the changing of output and inputs prices. As a result, this study suggests the needs to increase the non-agriculture job opportunities in rural area, such as rural industrialization programs, in order to absorb the surplus labor forces.